2015
DOI: 10.15835/nsb729481
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cultural Conditions for Production of Antibacterial Metabolites from <i>Streptomyces coelicoflavus</i> BC 01

Abstract: The aim of the present study was to optimize various cultural conditions for the production of antibacterial metabolites by Streptomyces coelicoflavus BC 01 isolated from mangrove soil, Visakhapatnam, Andhra Pradesh, India. The effect of various factors such as carbon and nitrogen sources, different concentrations of NaCl and K2HPO4, different temperature, pH, incubation time and agitation on antibacterial metabolites production were studied. The production of antibacterial metabolites by the isolate Streptomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…KB1 (TISTR 2304) showed a narrow range of incubation temperatures for BC production and the most suitable incubation temperature for the maximum production of BCs was 30 °C. This finding coincided with research by Raghavarao et al (2015) who reported that Streptomyces coelicoflavus BC01 could produce BCs at incubation temperatures between 15 °C to 45 °C, but the optimal temperature was 30 °C. In addition, this finding was in accordance with the results of Bundale et al (2015) who reported that the optimal temperature for the production of BCs for the three Streptomyces species in their study was 30 °C.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…KB1 (TISTR 2304) showed a narrow range of incubation temperatures for BC production and the most suitable incubation temperature for the maximum production of BCs was 30 °C. This finding coincided with research by Raghavarao et al (2015) who reported that Streptomyces coelicoflavus BC01 could produce BCs at incubation temperatures between 15 °C to 45 °C, but the optimal temperature was 30 °C. In addition, this finding was in accordance with the results of Bundale et al (2015) who reported that the optimal temperature for the production of BCs for the three Streptomyces species in their study was 30 °C.…”
Section: Resultssupporting
confidence: 90%
“…This finding was in accordance with research from Augustine, Bhavsar & Kapadnis (2005) who reported that Streptomyces rochei AK39 could produce the maximum amount of cephalosporin C at an agitation rate of 200 rpm. Moreover, this finding also coincided with research from Raghavarao et al (2015) who reported that the production of antibacterial metabolites by Streptomyces coelicoflavus BC01 decreased when agitation speed increased ( Raghavarao et al, 2015 ). The decrease of BC production of Streptomyces species at high agitation speeds indicated that it was affected by the death or damage of cells by shearing forces caused from agitation at high speed ( Lee et al, 2014 ).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations